2013
DOI: 10.4038/seajme.v7i1.150
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the achievement of the National License Examination Part 1 of medical students in Faculty of Medicine Vajira Hospital, Navamindradhiraj University

Abstract: Introduction: National License Examination (NLE) is organized by the Consortium of Thai Medical Schools to assess the competency of medical students. Part I-NLE involves an evaluation of basic science knowledge. Our objective was to evaluate factors associated with the results of part-I NLE. Methods: Learning attitude and behavior, preparation for and attitude towards the NLE were surveyed by a questionnaire given to all third to fifth year students (in 2010) at the institution. Additional data collected were:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
2
2
0
Order By: Relevance
“…For multiple linear regression analyses, the comprehensive examination score and scores of subjects taught in the first and the second preclinical years, especially gross anatomy and pharmacology scores, contributed significantly to the models predicting the NLE1 score. Our results were consistent with previous studies showing that the higher comprehensive score (16,38), GPA (31), and academic performance (38) were associated with the higher score of the national license examination. These results suggest that academic achievement during regular classes and a comprehensive examination had very strong associations with the NLE1 score.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For multiple linear regression analyses, the comprehensive examination score and scores of subjects taught in the first and the second preclinical years, especially gross anatomy and pharmacology scores, contributed significantly to the models predicting the NLE1 score. Our results were consistent with previous studies showing that the higher comprehensive score (16,38), GPA (31), and academic performance (38) were associated with the higher score of the national license examination. These results suggest that academic achievement during regular classes and a comprehensive examination had very strong associations with the NLE1 score.…”
Section: Discussionsupporting
confidence: 93%
“…Correlation analyses showed that both NLE1 and comprehensive examination scores were positively correlated with percentile of exam expectation and were negatively correlated with nonacademic internet use in the regular period (h/day) and stress level in the period approaching the NLE1. Our results were consistent with a previous study showing that good learning behavior and good exam preparation were positively correlated with the higher NLE1 score (31). Furthermore, the results regarding time spent on nonacademic internet use corresponded with a previous study showing that the higher time spent on internet use for nonacademic purposes was associated with the lower academic performance (29).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The first step of the MLE focuses on basic science knowledge, the second step on clinical science knowledge, and the third step on both knowledge and clinical skills evaluation. This is to standardize the basic competencies of graduate physicians and to assure health consumers have a standard health care service 8 .…”
Section: Introductionmentioning
confidence: 99%